Carl Philipp Emanuel Bach: Dokumente zu Leben und Wirken aus der zeitgenössischen Hamburgischen Presse (1767-1790) - Wiermann, Barbara (Hildesheim New York Olms, 2000)
The texts, compiled from three daily newspapers and various (scholarly) journals, provide new biographical details, document the progress of Bach's publication projects, provide insights into his activities as Hamburg's music director, convey a lively picture of the Hamburg concert scene and shed light on Bach's position in the musical life of his time.
Includes bibliographical references and indexes.
Keywords: Bach, Carl Philipp Emanuel -- 1714-1788; 18th Century (1701-1800); Music history; Music criticism; Hamburg (Germany)